Cutaneous Pili Migrans: A Rare Case from North India - Ipshita Bhattacharya; Tapan Dhali; Paschal Dsouza; Vishnu Choudhary (Nepal Journal of Dermatology, Venereology & Leprology)
Cutaneous Pili Migrans (CPM) is a rare creeping eruption with only 40 cases reported so far. CPM is defined as a condition where a hair shaft or fragments gets embedded in superficial skin. It is known to affect both adults and children. We report a 23-year-old male patient who presented with sudden sharp pain in the foot on walking. Cutaneous examination revealed a black linear thread-like lesion on the medial plantar aspect of the right great toe associated with mild to moderate tenderness. The particle was removed by superficial paring along with gentle forceps extraction. Microscopic examination confirmed it to be a hair shaft fragment. While the exact etiology of CPM is unclear, it is proposed to be an acquired condition. Since it can mimic other creeping eruptions like Larva migrans, it is important to be aware of this condition.